Providing alternative reinforcers to facilitate tolerance to delayed reinforcement following functional communication training. Issue 3 (11th May 2015) - Austin, Jillian E.; Tiger, Jeffrey H.
<x xml:space="preserve">Abstract</x> The earliest stages of functional communication training (FCT) involve providing immediate and continuous reinforcement for a communicative response (FCR) that is functionally equivalent to the targeted problem behavior. However, maintaining immediate reinforcement is not practical, and the introduction of delays is associated with increased problem behavior. The present study evaluated the effects of providing alternative reinforcers during delays to reinforcement with a 13‐year‐old boy with an intellectual disability. Problem behavior was less likely when alternative reinforcers were available during delays.